ASSISTANCE IN MAKING DIGITAL FINANCIAL REPORTS AT UD. BEHIND THE NAME - Rhiana, Dynda Novi; Putri, Putu Indah Dianti; Wedagama, Dewa Ayu Trisna Adhiswari (LPPM Univ. Ibn Khaldun Bogor, 2023)
Financial reports are very important for the running of a company. Quality financial reports must be relevant and reliable. In this digital era, financial reports can be easily applied to software that is easily accessible to the general public, such as Google Sheets. UD. Behind The Name is a garment company engaged in the production of clothing so far still uses bookkeeping for financial reports. The application of digital financial reports will make it easier for users, and report readers and will also make it easier to calculate, as well as record. Improperness in writing financial statements can cause errors in the submission of reports that can cause losses due to miscalculations, or unreadable writing. Therefore, digital financial reports are very important, especially in an era that makes it easier for us to use technology. This is the background for the author to carry out service activities in the context of Field Work Practices by assisting the finance staff in making financial reports using Google Sheets.